Analisis Kinerja Keuangan dan Pergerakan Saham Emiten Farmasi di BEI Sebelum dan Saat COVID 19 - Dagna Puspabitha; Harsita Gianti; Muhammad Budi Nur Iman (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This article is written to present appropriate facts and data so that they can refute or justify these assumptions, regarding the capital market, investors after knowing whether the assumptions are valid or invalid they need to determine their attitude, whether to sell, buy or just wait and see. is quantitative research. Sources of data in this study using secondary data. The secondary data used in this study is the financial statements of each pharmaceutical sub-sector company in 2018, 2019, 2020. The data collection technique used in this study is the documentation method. The data analysis technique for financial performance used is the Wilcoxon Sign Test asymp value. there is no strong interest from investors and potential investors to make long-term sales or purchases, all are still waiting and see and these stocks are mostly open and close at prices that are not too high or low because many buy or sell in the short term to get profits or just beautify your portfolio with the expectation of future profit.